(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
This article analyzes the correlation relationships between the age of military personnel, their physical fitness level, and the results of performing test physical exercises. The study was conducted at the stage of basic military training with the participation of 273 military personnel, divided into age categories: 25–29, 30–34, 35–39, 40–44, and 45–49 years. The assessment of physical fitness was carried out on the basis of a specially developed methodology, which involved the performance of a complex of physical tests. Using correlation analysis with the non-parametric Spearman’s criterion, the peculiarities of age-related influence on the level of physical fitness were established, which made it possible to identify age groups in which a statistically significant relationship is observed. The results of the correlation analysis showed no statistically significant relationship between age and the level of physical fitness in military personnel aged 25–29 years (r = -0.204, p > 0.05), while strength exercises demonstrate high correlation relationships with the overall level of physical fitness (from r = 0.838 to r = 0.917, p < 0.001). In the category of military personnel aged 30-34 years, age does not affect the results of test exercises, and the greatest correlation relationship with the level of physical fitness is observed for the test physical exercise of bending and unbending arms in a lying position (r = 0.928, p < 0.001). In military personnel aged 40-44 years, an inverse correlation relationship was found between age and the level of physical fitness (r = -0.352, p < 0.01), which indicates a tendency to decrease physical fitness at an older age. In the group of military personnel aged 45-49 years, an inverse correlation relationship of age with the level of physical fitness was also found (r = -0.287, p < 0.05), and the largest correlation relationships were noted for strength exercises (from r = 0.644 to r = 0.868, p < 0.001). Overall, the results indicate a significant impact of test exercises on the level of physical fitness and a tendency for it to decrease in older age groups.